Metformin inhibits mitochondrial adaptations to aerobic exercise training in older adults. Issue 1 (11th December 2018) - Konopka, Adam R.; Laurin, Jaime L.; Schoenberg, Hayden M.; Reid, Justin J.; Castor, William M.; Wolff, Christopher A.; Musci, Robert V.; Safairad, Oscar D.; Linden, Melissa A.; Biela, Laurie M.; Bailey, Susan M.; Hamilton, Karyn L.; et al.
Abstract: Metformin and exercise independently improve insulin sensitivity and decrease the risk of diabetes. Metformin was also recently proposed as a potential therapy to slow aging. However, recent evidence indicates that adding metformin to exercise antagonizes the exercise‐induced improvement in insulin sensitivity and cardiorespiratory fitness. The purpose of this study was to test the hypothesis that metformin diminishes the improvement in insulin sensitivity and cardiorespiratory fitness after aerobic exercise training (AET) by inhibiting skeletal muscle mitochondrial respiration and protein synthesis in older adults (62 ± 1 years). In a double‐blinded fashion, participants were randomized to placebo ( n = 26) or metformin ( n = 27) treatment during 12 weeks of AET. Independent of treatment, AET decreased fat mass, HbA1c, fasting plasma insulin, 24‐hr ambulant mean glucose, and glycemic variability. However, metformin attenuated the increase in whole‐body insulin sensitivity and VO2 max after AET. In the metformin group, there was no overall change in whole‐body insulin sensitivity after AET due to positive and negative responders. Metformin also abrogated the exercise‐mediated increase in skeletal muscle mitochondrial respiration. The change in whole‐body insulin sensitivity was correlated to the change in mitochondrial respiration. Mitochondrial protein synthesis rates assessed during AET were not different between treatments. The influence of metformin on AET‐induced improvements in physiological function was highly variable and associated with the effect of metformin on the mitochondria. These data suggest that prior to prescribing metformin to slow aging, additional studies are needed to understand the mechanisms that elicit positive and negative responses to metformin with and without exercise.